Compliance to Islamic marketing practices among businesses in Malaysia - Abdullah, Kalthom; Sayyed Ahmad, Mohd. Ismail (Emerald Publishing Group, 2010)

(untitled)
Purpose – This research paper aims to explore the perceptions of Muslim consumers of the degree of compliance of Malaysian businesses to Islamic marketing practices and promotional strategies. Design/methodology/approach – The perceptions of the Muslim consumers were examined by distributing a self-administered survey questionnaire to a sample of 450 Muslim respondents residing in the major towns in Peninsular Malaysia. Items used in the questionnaire were derived from the basic guidelines provided in the Quran and the Sunnah on the conduct of business practices, specifically on the general marketing and promotional practices used. Findings – Findings suggest that though there is an awareness of these regulations and practices, not many businesses in Malaysia are perceived to be complying with them both with respect to general Islamic marketing principles and with recommended Islamic promotional practices. There was also a significant difference in opinions expressed by Muslim consumers due to the influence of their religious educational background and the states in which they resided. Practical implications – There is a need towards more research on how Islamic guidelines could be applied in all aspects of marketing activities. This could create more awareness among businesses about the issues and obligations that are relevant in marketing practices. Originality/value – This research is a rare attempt on the part of researchers and scholars in Malaysia to relate the Islamic injunctions and guidelines on a specific discipline such as marketing. Although there have been many studies on Islamic finance and economics, the area of Islamic marketing remains clearly under researched. Keywords Islam, Consumers, Individual perception, Marketing strategy, Promotional methods, Malaysia Paper type Research paper